2012
DOI: 10.1155/2012/968123
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-Autonomic Imbalance and Baroreflex Dysfunction in the Renovascular Angiotensin-Dependent Hypertensive Mouse

Abstract: Mouse models provide powerful tools for studying the mechanisms underlying the dysfunction of the autonomic reflex control of cardiovascular function and those involved in cardiovascular diseases. The established murine model of two-kidney, one-clip (2K1C) angiotensin II-dependent hypertension represents a useful tool for studying the neural control of cardiovascular function. In this paper, we discuss the main contributions from our laboratory and others regarding cardiac-autonomic imbalance and baroreflex dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 50 publications
4
28
0
2
Order By: Relevance
“…The findings obtained by this study corroborate our previous reports (Campagnaro et al, 2012 supporting the hypothesis that 2K1C hypertension might induce oxidative stress in nonspecific tissues, including the BM. Enhanced levels of oxygen radicals, which characterize a state of oxidative stress, have been described in clinical and preclinical studies in many cardiovascular diseases, including diabetes, hypertension, and atherosclerosis (Minuz et al, 2002;Porto et al, 2011;Silva et al, 2012;Vasquez et al, 2012;Luévano-Contreras et al, 2013).…”
Section: Oxidative Stresssupporting
confidence: 92%
See 3 more Smart Citations
“…The findings obtained by this study corroborate our previous reports (Campagnaro et al, 2012 supporting the hypothesis that 2K1C hypertension might induce oxidative stress in nonspecific tissues, including the BM. Enhanced levels of oxygen radicals, which characterize a state of oxidative stress, have been described in clinical and preclinical studies in many cardiovascular diseases, including diabetes, hypertension, and atherosclerosis (Minuz et al, 2002;Porto et al, 2011;Silva et al, 2012;Vasquez et al, 2012;Luévano-Contreras et al, 2013).…”
Section: Oxidative Stresssupporting
confidence: 92%
“…Some authors, including us, have observed alterations in DNA caused by hypertension (Schupp et al, 2007;Fandos et al, 2009;Campagnaro et al, 2012Campagnaro et al, , 2013. In this work, the DNA content analysis showed that 2K1C hypertension induces DNA fragmentation in BM cells, suggesting that the disease leads to DNA changes compromising the functionality of the cells.…”
Section: Dna Contentsupporting
confidence: 49%
See 2 more Smart Citations
“…A angiotensina 2 e a angiotensina 1-7 desempenham um importante papel em doenças crônicas como hipertensão renovascular e insuficiência cardíaca crônica (CAMPAGNARO et al, 2012). O desequilíbrio entre essas angiotensinas dentro do sistema renina angiotensina tecido específico (sistema nervoso central e periférico, renal e cardíaco) influencia na perda da função dos mecanismos de ajuste da PA. Em ambas as patologias, observa-se a perda de sensibilidade do barorreflexo e um desbalanço dos sistemas autônomos simpático e parassimpático.…”
Section: Vfc Representa Um Mau Prognóstico (Ribeiro and Moraes Filho 2unclassified